Using Kahoot Based Learning for Reading Excercises at Senior High School Muhammadiyah 4 Porong - Lestari, Santi Ayu Nanda; Aisyah, Siti; Prasetyo, Yudy (Journal of English Language and Education, 2026)
Low levels of active participation and learning motivation remain persistent challenges in English language classrooms that rely heavily on lecture-based instruction and textbook-centered practices. Such conventional approaches often create a monotonous learning environment, particularly in reading activities that require sustained attention and cognitive engagement. These conditions call for more interactive and learner-centered strategies that align with students’ digital learning preferences. One potential alternative is Kahoot!, a game-based quiz platform designed to promote competition, enjoyment, and immediate feedback. This article examines the implementation of Kahoot-based learning as an innovative strategy to enhance students’ reading exercises. Reading is a fundamental language skill; however, learners frequently encounter difficulties due to limited motivation and minimal engagement in traditional instructional settings. By integrating Kahoot into reading activities, classroom interaction becomes more dynamic, participatory, and student-centered. The study aims to investigate how Kahoot-based learning supports reading comprehension, vocabulary development, and learning motivation. The research method involves administering reading exercises through Kahoot quizzes and observing students’ responses and performance during the instructional process. The findings indicate that Kahoot-based learning increases active participation, strengthens motivation, and improves comprehension through instant feedback and competitive elements. Moreover, it fosters a positive classroom climate and encourages collaborative learning. Therefore, Kahoot-based learning represents an effective alternative strategy for improving students’ reading skills.